(untitled) (Shiksha Shastra Saurabh, 2018)
Translation is a process of rendering meaning from one language to another language and translation procedures are the technical strategies adopted by the translator to achieve the closet possible equivalent. In this paper an attempt has been made to evaluate the techniques of translation of cultural terms offered by New mark that have been employed in translating cultural words. This paper also aims to have an argument on the techniques of translation that focus on target readers in post-modernism. It has been found that in translating cultural terms, ten different techniques are found to have been employed in translating cultural words. Literal translation is mostly used and claque is the least used technique. There is triangular relationship among the translator, the text and the reader. A translator should remove the spectacle of domination and accept the foreign culture and source culture with respect in postmodernism.